SPELLING ERROR ANALYSIS IN WRITING RECOUNT TEXT BY THE NINTH-GRADE STUDENTS OF SMP NEGERI 1 SUMBAWA ACADEMIC YEAR 2022/2023 - M. Givan Fachrezzy; Sahuddin; Baharuddin (Journal of English Education Forum (JEEF), 2022)
The aims of this study are to find out the types of spelling errors made by the ninth-grade students of SMPN 1 Sumbawa by determining students writing and to find out the causes of spelling error made by students. In addition, this study uses the theory from Bestgen and Granger (2011) in their journal entitled “Categorizing Spelling Error to Assess L2 Writing” that discussed about the category of spelling errors. Furthermore, this research applies descriptive qualitative in which the researchers collected the data from students writing tasks and found the spelling error of three words classification which are adjective, noun and verb. The researchers found six types of spelling errors which are addition, omission, substitution, transposition, word segmentation, and multiple error letter. In addition, there are three main causes of spelling error found such as the influence of Indonesian spelling, lack of vocabulary, and spelling difficulties